Management of asthma in hospital: a prospective audit. Issue 6637 (11th June 1988) - Bucknall, C E; Robertson, C; Moran, F; Stevenson, R D
Abstract : In a prospective study of management of asthma in hospital patients with acute asthma admitted to a single hospital over a calendar year were surveyed. Altogether 157 out of 194 admissions (81%) were studied. The patients (16 of whom had been admitted twice and one three times) were interviewed at home about two weeks after discharge, and their hospital records were reviewed. When interviewed an appreciable proportion of patients said that their asthma had been poorly controlled after their discharge from the hospital: 54 reported regular sleep disturbance due to wheeze, 78 tightness of the chest in the morning, and 77 wheeze after climbing one flight of stairs. Patients had been described on admission as having had symptoms of deteriorating asthma for a median of three days. Closer questioning of 71 patients, however, elicited that 50 had had regular symptoms indicating poor control for weeks or months. Most patients did not know how their drugs worked, and many did not have an appropriate plan of action in the event of a further attack. In all the cases studied 114 patients were treated with oral corticosteroids, only 70 had had their previous maintenance treatment increased at the time of discharge, and 107 had a follow up appointment booked for an average of three and a half weeks after discharge. These findings show that undersupervision and undertreatment of patients with asthma are common and not confined to those dying of the condition.